Strategi Pendidikan Karakter Rasa Tanggung Jawab Peserta Didik Melalui Kegiatan Pramuka - Binti Sulyani (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to describe the Character Education Strategy for a Sense of Responsibility for students. The method of this research is a qualitative approach.